2019
DOI: 10.12998/wjcc.v7.i11.1253
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and immunotherapy in gastrointestinal tumors: Friend or foe?

Abstract: The incidence of gastrointestinal (GI) tumors is increasing year by year, and its pathogenesis is closely related to the intestinal flora. At present, the use of antibiotics is very common in the clinic. And cancer patients with low immunity are vulnerable to all sorts of infections, such as respiratory tract infections and urinary tract infections. Moreover, cancer patients easily run into fever and neutropenia induced by myelosuppression. Therefore, antibiotics are used extensively and even overused in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The blue terms emerged first, followed by the yellow and green terms that appeared later Furthermore, the increase in the number of publications on microbiota and cancer may be linked to many hot topics published during this time frame, exposing innovative theories that lead to new fields of research. These findings suggest new therapeutic and diagnostic concepts for various disorders in the field of oncology [38][39][40][41][42][43][44][45][46][47][69][70][71][72][73] such as "effect of probiotics on cancer", "microbiota composition and gene expression" and "hostmicrobiome interaction in cancer immunotherapy".…”
Section: Discussionmentioning
confidence: 96%
“…The blue terms emerged first, followed by the yellow and green terms that appeared later Furthermore, the increase in the number of publications on microbiota and cancer may be linked to many hot topics published during this time frame, exposing innovative theories that lead to new fields of research. These findings suggest new therapeutic and diagnostic concepts for various disorders in the field of oncology [38][39][40][41][42][43][44][45][46][47][69][70][71][72][73] such as "effect of probiotics on cancer", "microbiota composition and gene expression" and "hostmicrobiome interaction in cancer immunotherapy".…”
Section: Discussionmentioning
confidence: 96%
“…[11][12][13] From 2017 onwards, several retrospective and prospective clinical studies then evaluated the association between antibiotics and the efficacy of immunotherapy. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] All of these studies showed significantly worse progression-free and/or overall survival in the group of patients exposed to antibiotics. The relative decrease in median overall survival ranged from 3.8 to 16.7 months.…”
Section: Introductionmentioning
confidence: 99%
“…The data from these small perspective studies can be extrapolated into immunotherapy treatment of microsatellite instability–high CRC patients because there are no data on this association from any known perspective analysis. In a retrospective analysis including different gastrointestinal cancers, such as CRC, Yan et al found that antibiotics adversely affect the gut microbiome and influence the development and progression of cancer, especially CRC [ 52 ]. Different strains of bacteria are connected to different gastrointestinal (GI) tumours; for example, enterotoxigenic Bacteroides fragilis is connected to CRC [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different strains of bacteria are connected to different gastrointestinal (GI) tumours; for example, enterotoxigenic Bacteroides fragilis is connected to CRC [ 53 , 54 ]. Previous studies have shown the correlation between the efficiency of immunotherapy and the abundance of these specific strains of bacteria, such as Bifidobacterium longum or Ruminococcaceae bacteria [ 52 54 ]. Thus, it is possible to influence immunotherapy responsiveness by manipulating gut microbiota.…”
Section: Introductionmentioning
confidence: 99%